Time or state dependent price setting rules? Evidence from Portuguese micro data - Daniel Dias; Carlos Robalo Marques; Jo\~ao M. C. Santos Silva (European Central Bank (ECB), 2005)
In this paper we analyse the ability of time and state dependent price setting rules to explain durations of price spells or the probability of changing prices. Our results suggest that simple time dependent models cannot be seen as providing a reasonable approximation to the data and that state dependent models are required to fully characterise the price setting behaviour of Portuguese firms. Inflation, the level of economic activity and the magnitude of the last price change emerge as relevant variables affecting the probability of changing prices. Moreover, it is seen that the impact differs for negative and positive values of these covariates.
Keywords: C41; D40; E31; 330; CPI data; Hazard functions; inflation; Preisrigidität; Preismanagement; Inflation; Portugal